Kontribusi Modal Sosial pada Resiliensi Mental Komunitas di Zona Konflik Timur Tengah - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
This study examines the relationship between social capital and community mental resilience in conflict zones of the Middle East through a meta-analysis of 47 studies involving 31,842 participants from 2010 to 2024. Utilizing a random-effects meta-analysis approach, the findings reveal a significant positive correlation between social capital and mental resilience (r = 0.64, p < .001, 95% CI [0.58, 0.70]).